PENGELOLAAN DANA DESA DALAM MENINGKATKAN PEREKONOMIAN DI DESA LAMBELU, KECAMATAN PASIKOLAGA, KABUPATEN MUNA - Muhamad Tonasa; Wa Ode Sarbianti (Jurnal Kewirausahaan Bukit Pengharapan, 2025)
The existence of Law No. 6 of 2014 concerning Villages begins to show that the government has paid attention to villages. Management of Village Funds is regulated in the Regulation of the Minister of Home Affairs Number 113 of 2014 concerning Village Financial Management and Regulation of the Minister of Home Affairs Number 114 concerning Village Development as stated in Article 71 paragraph 1, it is stated that "all village rights and obligations that can be valued in money and everything in the form of money and goods related to the implementation of village rights and obligations" The purpose of this study was to determine how village funds are managed in Lambelu Village, Pasikolaga District, Muna Regency, and to explain how village funds are managed in Lambelu Village, Pasikolaga District, Muna Regency in terms of Islamic economics. This type of research uses qualitative descriptive research with data collection methods in the form of observation, interviews and documentation. The results of this study illustrate that the first is the management of village funds in improving the economy in Lambelu Village, Pasikolaga District, Muna Regency, namely the existence of mature planning, transparency, accountability, justice, community participation, the existence of an appropriate village fund budget for projects that support local economic development, efficient administration, accurate financial management, collaboration with external parties and supervision in the management of village funds so that all of this can be effective in improving the economy in Lambelu Village. The second is the management of village funds in Lambelu Village, Pasikolaga District, Muna Regency in the Islamic economic perspective, namely that it has complied with sharia principles with evidence of the APBDesa transparency board in the Lambelu Village hall, accountability, and justice in village funds to ensure community welfare and sustainable economic sustainability.